A faunal survey of macromoths (Lepidoptera : macroheterocera) on mount Serapi, Kubah National Park, Kuching, Sarawak - Jamilah, binti Ismail. (Universiti Malaysia Sarawak (UNIMAS), 2007)
The present study is based on a five-night sampling with twenty series of light-trap data of macromoth species on Mount Serapi. Kubah National Park, Sarawak in December 2006. Species composition of the total of 218 species identified from 903 individuals was investigated. From the families encountered, Geometridae (43.1 %) and Noctuidae (23.3%) represent the most speciose families followed by Arctiidae (\2.8%). Many species collected are considered common. Several infrequently encountered species and two endemic species to Borneo were also discovered. 116 species were considered as rare. Among the infrequent species are Semiothisops macariata and Zamarada nesiotica and the two endemics are Derambila livens and Spaniocentra megaspila. A checklist ofthe macromoth species on Mount Serapi is provided as a baseline catalogue.